2022
DOI: 10.26508/lsa.202201405
|View full text |Cite
|
Sign up to set email alerts
|

Genome-scale metabolic models for natural and long-term drug-induced viral control in HIV infection

Abstract: Genome-scale metabolic models (GSMMs) can provide novel insights into metabolic reprogramming during disease progression and therapeutic interventions. We developed a context-specific system-level GSMM of people living with HIV (PLWH) using global RNA sequencing data from PBMCs with suppressive viremia either by natural (elite controllers, PLWHEC) or drug-induced (PLWHART) control. This GSMM was compared with HIV-negative controls (HC) to provide a comprehensive systems-level metabo-transcriptomic characteriza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 58 publications
(86 reference statements)
0
9
0
Order By: Relevance
“…We also reported that by blocking two critical central metabolic pathways, glycolysis and glutaminolysis, viral replication and production were inhibited (Krishnan et al, 2021). Although systemic GSMM was not reported in other respiratory diseases caused by viruses, in our recent study to understand the natural control of HIV-1 infection, we observed the regulation of similar metabolic pathways, but the difference in the metabolic reactions potentiates a disease-specific contextualization of the metabolic flux (Ambikan et al, 2022). A viral disease-specific systemic GSMM atlas for other emerging and re-emerging viruses is underway.…”
Section: Articlementioning
confidence: 75%
“…We also reported that by blocking two critical central metabolic pathways, glycolysis and glutaminolysis, viral replication and production were inhibited (Krishnan et al, 2021). Although systemic GSMM was not reported in other respiratory diseases caused by viruses, in our recent study to understand the natural control of HIV-1 infection, we observed the regulation of similar metabolic pathways, but the difference in the metabolic reactions potentiates a disease-specific contextualization of the metabolic flux (Ambikan et al, 2022). A viral disease-specific systemic GSMM atlas for other emerging and re-emerging viruses is underway.…”
Section: Articlementioning
confidence: 75%
“…We also developed a context-specific system-level Genome-Scale Metabolic Model (GSMM) using global RNA sequencing data on blood cells from PLWH that had suppressive viremia by natural mechanisms (EC) or drug-induced suppression (PLWH on cART) [81]. To provide a comprehensive system-level characterization, this GSMM was also compared to HIV-negative controls.…”
Section: System Biological Studies Defining the Immune Aging In Plwhmentioning
confidence: 99%
“…Recent gene-expression studies have indirectly evaluated the effects of cART, however: transcriptomic profiles of peripheral blood mononuclear cells (PBMCs) from PWH on suppressive cART may differ significantly from the PBMC profiles in elite HIV controllers, who are naturally virally suppressed without treatment. These transcriptomic studies suggest that inhibition of mitochondrial oxidative phosphorylation contributes to a larger reservoir size during cART [65][66][67]. The changes observed in non-controllers include upregulated glycolysis and glutaminolysis, which are proposed to contribute to accelerated senescence in latently infected immune cells during cART.…”
Section: Discussionmentioning
confidence: 93%